Cross Sectional Study on Awareness About Eye Banking in Moradabad (India) - Archana Chaudhary; Maitri Paul; Ashi Khurana; Lokesh Chauhan (Delhi Journal of Ophthalmology)
Purpose: There has been a shortage of transplantable corneal tissue in developing countries. Assessing awareness about eye banking would help us in making effective strategies to overcome this. Methods: A cross-sectional descriptive study was conducted using a standard pretested closed-ended structured questionnaire. Survey interview was conducted by an independent trained interviewer. Questionnaire had eighteen questions to assess awareness (6 questions), knowledge (6 questions) and process (6 questions) of eye donation. Results: A total of 396 individuals of more than 18 years participated in this survey. A total of 269 (67.9%) participants were aware that eyes can be donated and 156 (39.4%) participants agreed to donate their eyes after their death. Of all, 251 (63.4%) were aware that family consent is needed for eye donation and 172 (43.4%) participants thought that one needs to come to an eye hospital for eye donation. Only 82 (20.7%) participants know an eye bank facility in their nearby area. Of all, 86 (21.7%) participants believed that eyes can be donated by a living person and 24 (6.1%) believed that they need to pay for eye donation. Conclusion: Majority of participants know that eyes can be donated. However a low percentage of them agreed to donate their eyes after death. Awareness was low in terms of knowledge and process of eye banking. To increase awareness, innovative community based strategies to be implemented in the study area which ultimately increase cornea retrieval.